(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article describes a stone coffin and the grave goods found surrounding it. The author particularly focuses on the jet beads found and speculates that these may indicate that this was the grave of a high-ranking woman. He also briefly touches on other finds in the area as well as some local history.